PENGARUH BRAND IMAGE DAN BRAND LOVE TERHADAP BRAND COMMITMENT DAN POSITIVE WORD-OF-MOUTH PADA KONSUMEN SOMETHINC - Widarmanti, Tri; Anita yulianti (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2023)
Oral communication, known as "word of mouth", It’s considered the largest and foremost customer communication tool. It can influence the choice of where to buy, the products purchased, and the customer's opinion of certain goods and services. As a form of mass communication, positive word of mouth can arise when customers already have brand commitment as represented by their brand image and brand love. This research is to analyze the impact of brand love and brand image for brand commitment empirically on word of mouth. Our research was conducted using Somethinc objects with a sample of Somethinc product consumers. This descriptive and quantitative method was used in this study using the Partial Least Squares method. Collected data is done by using a questionnaire with an ordinal scale. The respondents' characteristics showed that the majority were somethinc product users with a percentage of female gender as much as 95.2%, age 21-24 years 57.4%, and have jobs as students as much as 67%. The analytical results show a positive relationship between brand love to brand image, brand commitment, and positive WOM, a positive relationship between brand love to brand commitment and positive WOM, to brand commitment to positive WOM, and a positive relationship between brand commitment to positive WOM.